2013
DOI: 10.21608/jappmu.2013.71020
|View full text |Cite
|
Sign up to set email alerts
|

Egg Yolk Cholesterol and Productive Performance of Laying Hens Influenced by Dietary Crude Fiber Levels Under Drinking Natural Saline Water

Abstract: This study was conducted to investigate the influenced of four levels of dietary crude fibers (CF) on egg yolk cholesterol, productive and physiological performance of laying hens under drinking natural saline water (2000 ppm total dissolved solids). A total number of 120 White Leghorn layers from 44 to 56 weeks of age randomly divided into four equal groups (30 hens of each). Four levels of CF (3, 4, 5 and 6 %) as substitution of alfalfa meal. The treatments were tested for 12 weeks. The results showed that u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In the present study, the availability of cholesterol in blood serum was found significantly different between SB2 and basal treatment (p<0.01). This was probably due to the higher intake of fibrous diets in basal treatment which is responsible for lowering the cholesterol content in serum [ 15 ]. In addition, serum proteins constitute a portion of the amino acid pool in the body, and it is believed to be indicative of the nutritional status of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the availability of cholesterol in blood serum was found significantly different between SB2 and basal treatment (p<0.01). This was probably due to the higher intake of fibrous diets in basal treatment which is responsible for lowering the cholesterol content in serum [ 15 ]. In addition, serum proteins constitute a portion of the amino acid pool in the body, and it is believed to be indicative of the nutritional status of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…Braz et al (2011) did not observe any differences on Haugh units and eggshell percentage when fed diets with different neutral detergent fiber (NDF) levels to layers. Hassan et al (2013) using above 3 % CF noticed higher (P<0.05) values of albumen height and shape index values with no significant differences in yolk index (%) and Haugh units.…”
Section: Cholesterol Concentration Within Eggs Serum and Organsmentioning
confidence: 77%
“…Zhang et al, (2005) explained that the role of cellulose is to direct bile acid from the intestine to the body, causing the formation of bile acids by extracting cholesterol from the blood, which causes a decrease of the cholesterol content. Hassan et al (2013) obtained a significant decrease in serum total lipids, cholesterol, triglyceride and HDL values with increasing (4%, 5%, 6%) CF levels.…”
Section: Cholesterol Concentration Within Eggs Serum and Organsmentioning
confidence: 81%
See 1 more Smart Citation
“…The cholesterol was significantly lower in the group R3 than control R1 and R2. This may be due that groups of FWOC had higher content of dietary fiber implicated causing reduction in serum and body cholesterol which referred to a natural hypocholesteremic agent (Hassan et al, 2013). Mustafa (2011) reported that cholesterol concentration was significantly decreased with high level addition of olive cake and this may due to that olive cake contains high level of omega-3 fatty acids which responsible for decreasing level of cholesterol concentration.…”
Section: Blood Parametersmentioning
confidence: 99%